Non-functioning adrenocortical carcinoma requiring radical nephrectomy-case report with review of literature - Karthik, Abishek H.; A. R., Bhaskarapprakash; R., Radhakrishnan; B., Natarajan; V., Selvaraj (International Journal of Research in Medical Sciences, 2023)
Adrenocortical carcinoma (ACC) is rare malignancy of the adrenal gland and is the second most aggressive endocrine malignant disease after anaplastic thyroid carcinoma. These tumours can be detected very late as majority are non-functional, i.e., does not secrete any hormones, and only present with vague symptoms. Surgical management of such tumours can be challenging as it can invade the surrounding structures making it very difficult for resection. This is a case of a 61-year male with a large non-functioning adrenal tumour which appeared to be separate from the kidney in the radiological imaging but was found stuck to the renal parenchyma posing a dilemma for the operating team.